Television programmes of eductional place on the children "samples of Sesame Street" - Yılmaz, Selin (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2016)
In this study, television programmes effect watched on the children. The children aged 2 - 6/7 years were examined the effect of educational level of visual and auditory perception. The perception of children of pre - operational power is high. Period is the most powerful level of intelligence and perception. They try to perceive and sense objects. Sesame Street program as research sample was examined.
Keywords: intelligence; perception; visual; auditory; Sesame Street; TV programmes